2017
DOI: 10.9755/ejfa.2017-02-274
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical and Functional Properties of Dietary Fiber From Bamboo Shoots (Phyllostachys Praecox)

Abstract: Dietary fiber are non-digestible constituents of plant cell walls, and comprise a necessary component of diet and its positive connection with human health. Till now, there is no report about the extraction and physicochemical and functional properties of dietary fiber from bamboo shoots. To find the potential applications of dietary fiber from bamboo shoots in food and health products, the effects of chemical, enzymatic methods and particle size distribution on the chemical and structural composition, physico… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 37 publications
2
22
0
Order By: Relevance
“…The yield of Sample 1 (42.02%) was higher than Sample 2 (36.71%) and Sample 3 (35.39%) which might be due to the insufficient degradation of starch as Wang et al . () had reported that α‐amylase could rapidly increase starch hydrolysis. Compared with the control, the high‐speed dispersion (in Sample 1) remarkably increased the dietary fibre content with a decrease of protein.…”
Section: Resultsmentioning
confidence: 99%
“…The yield of Sample 1 (42.02%) was higher than Sample 2 (36.71%) and Sample 3 (35.39%) which might be due to the insufficient degradation of starch as Wang et al . () had reported that α‐amylase could rapidly increase starch hydrolysis. Compared with the control, the high‐speed dispersion (in Sample 1) remarkably increased the dietary fibre content with a decrease of protein.…”
Section: Resultsmentioning
confidence: 99%
“…Initially, the starting temperature of the sample was 30 °C. After holding at 30 °C for 1 min, sample was heated to 90 °C at a rate of 10 °C/min [18]. The following thermodynamic parameters were recorded:…”
Section: Methodsmentioning
confidence: 99%
“…The wide peak at around 3,400 cm −1 was derived from the stretching vibration of ‐OH groups of cellulose and hemicellulose molecules (Khawas & Deka, 2016). Compared with RIDF, D‐RIDF and C‐RIDF had obvious blue shift at the frequency band, which might be related to the destruction of organic molecules of hydrogen bonds (Wang et al., 2017). The peak at 2,920 cm −1 was mainly due to the stretching vibration of C–H of carbohydrate methylene (Zhang et al., 2019).…”
Section: Resultsmentioning
confidence: 99%